Implementasi Pengelolaan Zakat Produktif Sebagai Upaya Penguatan Ekonomi Pasca Pandemi Covid19 Study pada Baznas Kabupaten Paser - Amrizal; Arbain; Agus Salim (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Zakat funds are collected from zakat maal funds for employees of the State Civil Apparatus in Paser Regency and distributed in the form of Consumptive and Productive Alms Infak Zakat Funds. The purpose of this study is to analyze and study the management of zakat infak and alms funds at the Amil Zakat Board of Paser Regency, as well as to analyze the effectiveness of zakat infak and alms management. The object of this research is the National Amil Zakat Agency in Paser Regency. The research design uses qualitative analysis with collective data by conducting in-depth interviews, documentation and observation. While the research informants consisted of administrators of the National Amil Zakat Agency and Muzaki who received productive zakat funds. Data analysis uses descriptive qualitative with the help of Nvivo12 Plus software. The research results prove that the source of zakat infaq and alms fund collection at the National Amil Zakat Agency in Paser Regency comes from professional zakat and Infaq from the State Civil Apparatus, there have been no other efforts to collect from other sources. The distribution of zakat, infaq and alms funds can help micro businesses, especially during the covid19 pandemic